Binary Solvent Regulated Architecture of Ultra‐Microporous Hydrogen‐Bonded Organic Frameworks with Tunable Polarization for Highly‐Selective Gas Separation. (13th February 2022) - Ding, Xiaojun; Liu, Zeyu; Zhang, Yusheng; Ye, Gang; Jia, Jianfeng; Chen, Jing
Abstract: A binary solvent synthetic strategy is proposed for the construction of C2 ‐symmetric molecule‐based hydrogen‐bonded organic frameworks (HOFs) with permanent ultra‐micropores and surface polarization derived from tunable coplanar open oxygen atoms. The activated HOFs BTBA‐1 a and PTBA‐1 a show highly selective separation of CO2 /N2 with a record high ideal adsorbed solution theory (IAST) selectivity >2000 under ambient temperature and pressure. Abstract : A series of ultra‐microporous hydrogen‐bonded organic frameworks (HOFs) with controlled open coplanar carboxyl oxygen atoms within the pores have been constructed through an adaptable binary solvent synthetic strategy. Activated HOFs with enhanced surface polarization show highly selective adsorption of CO2 over N2 based on differences of molecule polarizability.